Mixing nanostructured Ni/piezoPVDF composite thin films with e-beam irradiation: A beneficial synergy to piezoelectric response. (September 2021) - Potrzebowska, Natalia; Cavani, Olivier; Oral, Ozlem; Doaré, Olivier; Melilli, Giuseppe; Wegrowe, Jean-Eric; Clochard, Marie-Claude.
Graphical abstract: Abstract: Piezoelectric PVDF polymer thin films are nanostructured by swift heavy ion beam resulting in nanoporous structures. The nanocylindars are then partially filled with Ni(0) in order to create a composite of higher dielectric permittivity. In a second step, the composite is irradiated with electron beam, in order to induce chain scissions in the PVDF matrix and render it more flexible. It is found that e-beam irradiation does not affect the remanent polarization up to more than 1MGy. The energy harvesting properties are optimized with a maximum for 1MGy irradiation, delivering an output voltage of 4.1 V.cm −2 which corresponds to a maximum output power of 25μW. cm -2 and an integrated power of 0.46μW. cm −2 for 1 bar of external pressure (mechanical solicitations frequency of 10 Hz). The mechanisms responsible for the enhancement of the harvesting efficiency due to e-beam irradiation are discussed.